'Mahāwitthayālai' phalang khapkhlư̄an rabop sukkhaphāp chumchon : rūaprūam læ rīaprīang čhāk wēthī sēwanā "rūam phatthanā rabop sukkhaphāp chumchon" khrang thī 4 "Sathāban Wichākān kap Kānphapkhlư̄an Rabop Sukkhaphāp Chumchon", Wanʻangkhān thī 27 Thanwākhom 2554 na Hō̜ngprachum Bunsiri, Sathāban Phatthanā Sukkhaphāp ʻĀsīan, Mahāwitthayālai Mahidon (Samnakngān Wičhai læ Phatthanā Rabop Sukkhaphāp Chumchon, Sathāban Phatthanā Sukkhaphāp ʻĀsīan, Mahāwitthayālai Mahidon, 2012)
Proceedings of the 4th community-based health care system development forum on the empowerment and encouragement of countrywide universities' students to help drive and operate participatory activities for the development of community health care system in Thailand.